Exclusionary Government Rhetoric and Migration Intentions - Pawel Adrjan; Jan Gromadzki (Institute of Labor Economics (IZA), 2025)
We investigate whether exclusionary government rhetoric targeting a minority group affects residents' migration decisions. In 2019, almost 100 local governments in Poland voted to declare their localities "free from LGBTQ ideology," providing a unique setting in which government narratives suddenly changed, but the legal situation of targeted minorities remained the same. We study the impact of these resolutions on migration intentions using novel data on domestic and international job search from a large global job site. Comparing counties with anti-LGBTQ resolutions to neighboring counties in a difference-in-differences design, we find that the resolutions increased domestic out-of-county job search by 12 percent and international job search by 15 percent. Our results are likely driven by the shock to beliefs about local social norms, as we find the largest effects in counties with relatively low prior support for far-right parties. We also present suggestive evidence that the rise in job search translated into actual migration, with the treated counties losing nearly 1 percent of their young adult population.
Keywords: F22; R23; N40; J15; 330; migration; migration intentions; job search; discrimination; LGBTQ